MEMBANGUN HUMANISME TEOSENTRIS PADA ANAK MADRASAH IBTIDAYAH DALAM MERDEKA BELAJAR - M Fatwa; Istinaroh; Nur Khasan; Mukhrodi (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
Education in Madrasah Ibtidaiyah should foster faith awareness, creativity, and noble character, not merely memorization, by balancing cognitive, emotional, and spiritual aspects. The learning process needs to be more democratic so that children can develop their potential, character, and personality in accordance with their natural disposition through a theocentric humanism approach that integrates human values and divine unity. Theocentric humanism in Madrasah Ibtidaiyah within the independent learning framework emphasizes developing children’s natural disposition as active subjects oriented toward God, with the principle of life balance. Its implementation can be realized through methods such as playing, storytelling, singing, role modeling, and habituation both inside and outside the classroom. The ultimate goal is to shape a generation with noble character (akhlaq karimah), growing holistically and grounded in monotheism (tawhid).